Hyperoxia Improves Repeated-Sprint Ability and the Associated Training Load in Athletes - Shannon Cyr-Kirk; François Billaut (Frontiers Media S.A., 2022)
This study investigated the impact of hyperoxic gas breathing (HYP) on repeated-sprint ability (RSA) and on the associated training load (TL). Thirteen team- and racquet-sport athletes performed 6-s all-out sprints with 24-s recovery until exhaustion (power decrement ≥ 15% for two consecutive sprints) under normoxic (NOR: FIO2 0.21) and hyperoxic (HYP: FIO2 0.40) conditions in a randomized, single-blind and crossover design. The following variables were recorded throughout the tests: mechanical indices, arterial O2 saturation (SpO2), oxygenation of the vastus lateralis muscle with near-infrared spectroscopy, and electromyographic activity of the vastus lateralis, rectus femoris, and gastrocnemius lateralis muscles. Session TL (work × rate of perceived exertion) and neuromuscular efficiency (work/EMG [Electromyography]) were calculated. Compared with NOR, HYP increased SpO2 (2.7 ± 0.8%, Cohen's effect size ES 0.55), the number of sprints (14.5 ± 8.6%, ES 0.28), the total mechanical work (13.6 ± 6.8%, ES 0.30), and the session TL (19.4 ± 7.0%, ES 0.33). Concomitantly, HYP increased the amplitude of muscle oxygenation changes during sprints (25.2 ± 11.7%, ES 0.36) and recovery periods (26.1 ± 11.4%, ES 0.37), as well as muscle recruitment (9.9 ± 12.1%, ES 0.74), and neuromuscular efficiency (6.9 ± 9.0%, ES 0.24). It was concluded that breathing a hyperoxic mixture enriched to 40% O2 improves the total work performed and the associated training load during an open-loop RSA session in trained athletes. This ergogenic impact may be mediated by metabolic and neuromuscular alterations.